The Dendritic Cell-Regulatory T Lymphocyte Crosstalk Contributes to Tumor-Induced Tolerance. (3rd November 2011) - Janikashvili, Nona; Bonnotte, Bernard; Katsanis, Emmanuel; Larmonier, Nicolas
Abstract : Tumor cells commonly escape from elimination by innate and adaptive immune responses using multiple strategies among which is the active suppression of effector immune cells. Regulatory T lymphocytes (Treg) and tolerogenic dendritic cells play essential roles in the establishment and persistence of cancer-induced immunosuppression. Differentiating dendritic cells (DCs) exposed to tumor-derived factors may be arrested at an immature stage becoming inept at initiating immune responses and may induce effector T-cell anergy or deletion. These tolerogenic DCs, which accumulate in patients with different types of cancers, are also involved in the generation of Treg. In turn, Treg that expand during tumor progression contribute to the immune tolerance of cancer by impeding DCs' ability to orchestrate immune responses and by directly inhibiting antitumoral T lymphocytes. Herein we review these bidirectional communications between DCs and Treg as they relate to the promotion of cancer-induced tolerance.